(untitled) (Research, Society and Development, 2021)
Introduction: Oncotic colpocytology is a preventive examination responsible for detecting one of the main diseases that affect women around the world, which is cervical cancer, in addition to other vaginal infections. It is a test of great importance in women’s health, but it still has low adherence, either because of low education, little access to information, as well as the reluctance to undergo the test. Given this context, it is of such importance to spread this subject through health literacy with a focus on promotion and prevention for greater adherence to this test. Objectives: To assess the importance of health literacy on oncotic colpocitology for increasing adherence to this test. Methodology: Integrative review carried out between February and November 2021. The searches were performed in the United States National Library of Medicine (PUBMED), Scientific Electronic Library Online (SCIELO), Medical Literature Analysis and Online Retrieval System (MEDLINE) databases, Initially, 700 articles were found, of which, after the exclusion criteria, 20 articles were included in the review. Final Considerations: Health literacy, through health professionals adjunct to students, is extremely relevant to the female population, favoring greater adherence to the Pap smear test and a better understanding of the knowledge of female intimate life, breaking stigmas and improving the knowledge of lay people.